Carbon Distribution in Low-Temperature Isothermal Iron-Based Martensite and Its Tetragonality - Gavriljuk, V.G.; Firstov, S.O.; Sirosh, V.A.; Tyshchenko, A.I.; Mogilny, G.S. (Металлофизика и новейшие технологии, 2016)
Carbon distribution in the as-quenched Fe—C martensite obtained after cooling down to 4.5 K is studied using Mössbauer spectroscopy. The location of carbon atoms in the one of three available sublattices of octahedral interstitial sites is established, whereas the partial occupation by carbon atoms of tetrahedral sites or octahedral sites in other sublattices is not confirmed. The ageing of virgin isothermal martensite starts during heating at temperatures above -50°C and leads to disappearance of single carbon atoms and their clustering in the α solid solution. In comparison with martensite obtained at room temperature, a decreased tetragonality of the low-temperature isothermal martensite and its partial recovery during ageing is observed. Based on the estimation of dislocation density and the absence of ε-carbide precipitation during subsequent tempering, a conclusion is made that plastic deformation occurs in the course of isothermal martensitic transformation because of the softness of the virgin martensite. Finally, a new interpretation of the abnormally low tetragonality is proposed, of which the essence is the capture and transport of immobile carbon atoms by gliding dislocations. As a result, a part of carbon is removed from the α solid solution and forms carbon atmospheres around the dislocations. The comparison of this hypothesis with available other ones is presented. Two possible reasons for partial recovery of tetragonality during ageing of virgin martensite are discussed: (i) the unfreezing of Snoek atmospheres created by gliding dislocations crossing the immobile carbon atoms at low temperatures and (ii) coherent stresses at the boundaries of the intermittent carbon-rich and carbon-depleted domains in the modulated structure of the aged martensite.